Mobility of electrons in a guasi-one-dimensional conducting channel on the liquid helium surface in the presence of a magnetic field - Sokolov, Guo-Qiang; Hai, N.; Studart, S. S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The influence of the transverse magnetic field on the electron mobility in a quasi-one-dimensional channel along the liquid-helium surface is investigated. The mobility calculations are carried out by using the Boltzmann kinetic equation and the criteria for the validity of this approach, which are different from those for two-dimensional systems, are established. Two different limiting regimes corresponding to different roles of the electron-electron interaction in the quasi-one-dimensional electron system are considered. The mobility is shown to be a decreasing function of the magnetic field. It is shown that the temperature dependence of the mobility in the presence of the magnetic field, as in the case of zero field, is a nonmonotonic function.